The Effect of BAP and NAA Combination on Callus Induction of Aglaonema Siam Aurora Leaf Explants in Vitro - Anjani, Dianita Dewi; Ratnawati (Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2023)
This research aims to determine the effect of the Naphthalene Acetic Acid and Benzyl Amino Purine combination on callus growth of Aglaonema Siam Aurora leaf explants and to determine the combination level at the most optimal concentration on the callus growth of Aglaonema Siam Aurora leaf explants. Observation variables included callus emergence time, explants percentage of formed callus, callus length, and explant life percentage. The explants that where used were the first young leaves explants from shoots that were opened, with 2x2 cut size. Results show that the addition of a NAA and BAP combination had an effect on . Combination of 1.2 ppm BAP + 1 ppm NAA treatment is the most optimum treatment for callus growth with a callus percentage of 87.5%, the callus start time at week 3, the average callus length is 0.77 mm and the percentage number of survived explants is 100%